2014
DOI: 10.1007/s00726-014-1885-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glutamine deficiency is associated with multiple organ failure in critically ill children

Abstract: A low plasma glutamine concentration (<420 µmol/L) is an independent risk factor for mortality in critically ill adult patients. Glutamine metabolism in children is less well characterized. However, pediatric ICU (PICU) mortality is low and, therefore, mortality is difficult to use as an endpoint. Here we evaluated if plasma glutamine concentration at admission to the PICU, relates to the development of multiple organ failure, using pediatric logistic organ dysfunction score (PELOD)-score. In this observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…For example, severely ill neonates have low plasma Gln concentrations (79,80). It was also recently shown that low plasma Gln levels in critically ill children are associated with a higher incidence of multiple organ failure and longer duration of stay in the pediatric intensive care unit (53). Results presented here extend these previous investigations by demonstrating that children with SMA have significantly lower plasma Gln levels, and that low circulating Gln concentrations are associated with a highly significant increase in the risk of developing severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, severely ill neonates have low plasma Gln concentrations (79,80). It was also recently shown that low plasma Gln levels in critically ill children are associated with a higher incidence of multiple organ failure and longer duration of stay in the pediatric intensive care unit (53). Results presented here extend these previous investigations by demonstrating that children with SMA have significantly lower plasma Gln levels, and that low circulating Gln concentrations are associated with a highly significant increase in the risk of developing severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, low values of plasma glutamine can be associated with severe illness, in particular in children suffering from multiple organ failure in intensive care units (Ekmark et al 2015). …”
Section: Glutamine Deficiencymentioning
confidence: 99%
“…Medical conditions with pronounced protein catabolism (e.g., any life-threatening illness, severe inflammation, or burns) can also lead to reduction of the systemic glutamine pool [9,21]. However, glutamine levels reported in such cases remain higher than those seen in inherited GS deficiency [22]. …”
Section: Biochemical Presentationmentioning
confidence: 99%